Slow interatomic coulombic decay of multiply excited neon clusters - Iablonskyi, Denys; Nagaya, K.; Fukuzawa, H.; Motomura, K.; Kumagai, Y.; Mondal, S.; Tachibana, T.; Takanashi, T.; Nishiyama, T.; Matsunami, K.; Johnsson, P.; Piseri, P.; et al. (Physical review letters, 2016)
Ne clusters (∼5000 atoms) were resonantly excited (2p→3s) by intense free electron laser (FEL) radiation at FERMI. Such multiply excited clusters can decay nonradiatively via energy exchange between at least two neighboring excited atoms. Benefiting from the precise tunability and narrow bandwidth of seeded FEL radiation, specific sites of the Ne clusters were probed. We found that the relaxation of cluster surface atoms proceeds via a sequence of interatomic or intermolecular Coulombic decay (ICD) processes while ICD of bulk atoms is additionally affected by the surrounding excited medium via inelastic electron scattering. For both cases, cluster excitations relax to atomic states prior to ICD, showing that this kind of ICD is rather slow (picosecond range). Controlling the average number of excitations per cluster via the FEL intensity allows a coarse tuning of the ICD rate.
Gesehen am 28.04.2020